Oil Production Rehabilitation, Fiscal Policy and Economic Development in Libya: A Future View - Ali, Issa; Harvie, Charles (Energy Economics Letters, 2015)
This paper develops and simulates a dynamic general equilibrium macroeconomic model to analyze the likely impact of oil production and revenue rehabilitation on the Libyan economy, under different government fiscal policy responses. The model is ideally appropriate to analyze macroeconomic issues in oil-producing developing countries. In particular, it is capable of incorporating alternative government policy responses toward the allocation of the oil revenue either upon consumption spending or development spending in the form of government investment spending upon infrastructure, human capital formation and technology acquisition in non-oil production. It is also capable of incorporating different degrees of international capital mobility and other features that characterize oil-producing developing countries. We distinguish between the short-run and long-run impact of the oil production recovery upon the real exchange rate, price level, the non-oil trade balance, foreign assets, physical capital stock, human capital stock, imported capital stock and non-oil production. Based on recent development of oil production in Libya the paper finds that fiscal policy responses exert a crucial impact on the macroeconomic adjustment process. In particular, the implementation of a development oriented policy in the form of increased government expenditure upon infrastructure, human capital formation, and technological acquisition can transform the economy into a well-equipped one able to diversify and build a viable non-oil economy, and, therefore, to maintain and improve its competitive advantages. This eventually will result in noticeably improved economic outcomes and overall development of the economy.